Ritual and religious experience in early christianities: the spirit in between - McCollough, David John (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2022)
"In this volume, David John McCollough challenges the common assumptions that Paul thought the Spirit was communicated through water baptism, that 'justification' was non-experiential and unrelated to ritual, that Luke was incoherent or a poor editor, and that water baptism was the cardinal initiation rite among early Christianities." -- Publisher, page four of cover